Ocupação de áreas no entorno de mananciais e impactos sobre a qualidade da água: um estudo sobre a represa Billings (São Bernardo do Campo, SP) - Margarido, Natalia Takahashi [UNIFESP] (2019)
Given the double demand observed in the water source areas - having in one side population’s needs for housing, and in the other the necessity of water source protection to assure water supply -, the research aims to verify how occupied areas with different features, situated along the water source reservoir, have also different impacts concerning water quality, as a way to provide information that could improve public policy and environmental planning. Therefore, two areas of the Billings Reservoir’s margin in São Bernardo do Campo (SP) were studied: one of dense occupation, called Jardim Represa, and other of incipient occupation, called Capivari. They were distinguished according to socio-environmental features, such as time of residence in the area, water supply in the houses, expectations concerning the area, obtained via form research with local residents. Water quality monitoring was also held in those areas, and next to the water adduction in the reservoir as well, in the area known as Rio Grande. The monitoring of variables such as dissolved oxygen, orthophosphate and E. coli, among others, was done using an easy performing water quality test kit. Three scenarios were obtained by these means: i) related to the Jardim Represa area, of more intense impacts on water quality, ii) related to the Rio Grande area, of less intense impacts, and iii) related to the Capivari area, with an impact between the previous two. Along with the regression model stated with the socio-environmental features, that allows to obtain a measurable comparison in regard to the Jardim Represa’s situation, it was established a parallel between socio-environmental features and water quality, with the area of dense occupation associated to worse water quality. Moreover, the research could verify that even in areas where water quality presented better results concerning physicochemichal parameters, biological ones are also detected, being represented as more sensible to sewage dumps. It brings up attention to the health aspect as priority to environmental planning, that can be developed, for example, though environmental education initiatives.